2001
DOI: 10.4319/lo.2001.46.2.0331
|View full text |Cite
|
Sign up to set email alerts
|

Role of colloids and fine particles in the transport of metals in rivers draining carbonate and silicate terrains

Abstract: We have used cross flow filtration (CFF) to determine the pools of fine particulate (0.1-0.45 m), colloidal (1,000 Dalton to 0.1 m), and dissolved (Ͻ1,000 Dalton) metals in seven rivers that are all relatively rich in organic matter but have differing pH, alkalinity, and ionic strength. The metal content of Ͻ0.45-m filtered river water primarily reflects a mixing of two metal pools with differing elemental compositions: a truly dissolved pool and a colloidal pool. Fine particulate metals contribute Ͻ10% of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 46 publications
3
34
0
Order By: Relevance
“…Whilst the 0.45 Am threshold has become the accepted method of defining the dissolved load (McCleskey et al, 2004) and is used as such by EU directive 75/ 440/EEC, there is growing acknowledgment that it does not identify the true dissolved load (Danielsson, 1982). Work by Stordal et al (1996) and Hill and Aplin (2001) has shown colloidal materials to be effective adsorbers of metals and that metals present in b 0.45 Am filtrate may not be in a truly dissolved form.…”
Section: Solute Metal Concentrationsmentioning
confidence: 96%
“…Whilst the 0.45 Am threshold has become the accepted method of defining the dissolved load (McCleskey et al, 2004) and is used as such by EU directive 75/ 440/EEC, there is growing acknowledgment that it does not identify the true dissolved load (Danielsson, 1982). Work by Stordal et al (1996) and Hill and Aplin (2001) has shown colloidal materials to be effective adsorbers of metals and that metals present in b 0.45 Am filtrate may not be in a truly dissolved form.…”
Section: Solute Metal Concentrationsmentioning
confidence: 96%
“…The colloids in these samples were smaller than 8 m after passing through the glass wool filter. Filters with pore sizes of 0.45 and 0.1 m were used to separate the sample into different size fractions: soluble and nano-sized (PbS) (<0.1 m), fine colloid (PbF) (0.1-0.45 m) and coarse colloid (PbC) (0.45-8 m) [36][37][38]. After successively filtered through the two filters, the leachates of PbS and PbF fractions were digested following USEPA Method 3050a.…”
Section: Size Fractionmentioning
confidence: 99%
“…The major advantage of the method used is the very small size of the filter and low amount of pore space, which minimizes the adsorption inside the filter (Pokrovsky and Schott, 2002). Recovery (R) was calculated for all ultrafiltration runs (including blanks) as follows (Hill and Aplin, 2001):…”
Section: Stream-water Samplingmentioning
confidence: 99%